Insight into the effects of Omega-3 fatty acids on gut microbiota: impact of a balanced tissue Omega-6/Omega-3 ratio - Zou, Bo; Zhao, Dan; Zhou, Shuang; Kang, Jing X.; Wang, Bin (Frontiers in Nutrition, 2025)
Emerging evidence suggests that Omega-3 polyunsaturated fatty acids (PUFAs) are essential structural and functional nutrients that significantly influence the composition and function of the gut microbiota, a key mediator of host health. Although evidence suggests that increasing tissue Omega-3 levels through dietary intervention may optimize gut microbiota–host interaction through modulation of composition, metabolite production, and the intestinal mucus barrier, some studies have reported inconsistent findings regarding these protective effects. Studies indicate that a high Omega-6/Omega-3 ratio appears to attenuate the beneficial effects of Omega-3 supplementation on microbial diversity and abundance, while a balanced ratio fosters a more favorable microbiome profile. This review comprehensively highlights the potential effects of differential endogenous Omega-6/Omega-3 ratios on the gut microbiota-modulating capacity of Omega-3 PUFAs, which should be incorporated as a mandatory monitoring indicator in future clinical investigations. These insights provide a new direction for further optimizing the clinical application of Omega-3 PUFAs in chronic disease prevention and treatment.